Effects of Ionic Size and Hydrophobicity on Charging Dynamics at Microporous Pt. Issue 9 (1st September 2022) - Kim, Jinju; Shin, Jinsik; Yang, Hyun Ju; Kang, Chung Mu; Han, Donghoon; Bae, Je Hyun
Abstract : Nanoporous electrodes with extremely small pores have been developed for improved supercapacitors and electroanalysis. Ion transport into nanoconfined spaces has been studied using nanoporous carbon. Herein, we explore the size effect and hydrophobicity of ions on the charging dynamics using microporous Pt by cyclic voltammetry and electrochemical impedance spectroscopy. As the size of the effective hydrated ions decreased, the capacitance increased, and the movement of ions into and within the nanopores was less restricted. The effect of ionic size was more pronounced for hydrophobic organic cations than for hydrophilic alkali cations in microporous Pt. In addition, the microporous Pt electrode exhibited better performance in terms of capacitance and charging dynamics than the mesoporous carbon electrode when the hydrophilic electrolyte is dissolved in an aqueous solution. These findings provide insight into the formation of an electrical double layer at microporous metal electrodes and their applications in supercapacitors, electrocatalysts, and electroanalysis.